2013
DOI: 10.2527/jas.2012-5913
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of the effect of rubber slat mats on locomotory ability, body, limb and claw lesions, and dirtiness of group housed sows1

Abstract: This study evaluated the influence of floor type on sow welfare with particular focus on lameness, claw lesions (CL), and injuries. The study used 164 gilts housed in groups of 8 from AI to 110 d of pregnancy in pens with concrete (n = 84) slatted floor left uncovered or covered by 10-mm rubber slat mats (n = 80) through 2 parities. Lameness (0 = normal to 5 = severe), limb (0 = normal to 6 = severe) and body (0 = normal to 5 = severe) lesions, and manure on the body (MOB; score 0 to 2) were recorded at AI, 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 48 publications
2
32
0
Order By: Relevance
“…Rubber mats have been suggested to be a useful alternative for straw [32, 33]. Elmore et al [32] could not find a difference in lameness scores between sows housed on rubber mats versus concrete floors.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Rubber mats have been suggested to be a useful alternative for straw [32, 33]. Elmore et al [32] could not find a difference in lameness scores between sows housed on rubber mats versus concrete floors.…”
Section: Reviewmentioning
confidence: 99%
“…However, in that study, rubber mats were only added to the feeding stalls and not to the area with concrete slatted flooring between the stalls. By contrast, Díaz et al [33] covered the concrete slatted flooring in both the feeding stalls and the group area with rubber slat mats. Sows housed on rubber slat mats had a significantly reduced risk of becoming lame.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of claw lesions have often been performed on live pigs, either of varying age (Ehlorsson et al, 2002;Gjein and Larssen, 1995b;Olsson and Svendsen, 2002) or displaying a more limited age range (Díaz et al, 2013). Only a few studies on live animals have been complemented with studies on slaughtered gilts/sows, which were culled according to the normal routines in the herd and without systematic selection for a particular study (Gjein and Larssen, 1995b).…”
Section: Discussionmentioning
confidence: 99%
“…Claw lesions in live sows can be studied and scored on sows lying down in the farrowing room (Díaz et al, 2014), using equipment designed for claw trimming (Díaz et al, 2013;Olsson and Svendsen, 2002) or a mobile device for on-farm claw scoring (Van Riet et al, 2012). According to our experience (Olsson & Svendsen, 2002), scientific claw studies under the conditions found in practice are challenging.…”
Section: Discussionmentioning
confidence: 99%